2022
DOI: 10.3389/fpsyg.2022.805371
|View full text |Cite
|
Sign up to set email alerts
|

Safe-Sex Behavioral Intention of Chinese College Students: Examining the Effect of Sexual Knowledge Using the Theory of Planned Behavior

Abstract: Numerous contemporary studies have examined safe sexual behavior among college students. In China, families are reluctant to discuss sexual behavior, thus understanding and exploring the sexual knowledge of college students and the promotion of safe sexual behavior is essential. On the basis of the theory of planned behavior (TPB), a cognitive behavioral theory that is widely used to predict human social behavior, we conducted an in-depth investigation of the factors influencing the sexual behavioral intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…The average score of subjective norms in the test group significantly increased six months after the educational intervention, which is consistent with the study's findings. Several other studies have been read, including Khalajabadi Farahani et al [ 38 ], Mpeta et al [ 39 ], Wang et al [ 40 ], and Vatanchi et al [ 41 ]. In the current study, a family member of an addict attended one of the meetings and stressed their supportive role, which seemed to improve the test group's score on subjective norms.…”
Section: Discussionmentioning
confidence: 99%
“…The average score of subjective norms in the test group significantly increased six months after the educational intervention, which is consistent with the study's findings. Several other studies have been read, including Khalajabadi Farahani et al [ 38 ], Mpeta et al [ 39 ], Wang et al [ 40 ], and Vatanchi et al [ 41 ]. In the current study, a family member of an addict attended one of the meetings and stressed their supportive role, which seemed to improve the test group's score on subjective norms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has shown that Chinese families are unwilling to discuss sexual behavior. 40 While in the US, the rate of sexually active female college students was reported to be much higher than that of China 13 and quite a number of them had multiple sexual partners, which rendered them more susceptible to HIV, and they proactively exchange information about sex, including STD diseases such as AIDS, from their communication with parents, peers or friends. The results highlight the importance of re-examination of public and individual beliefs and understandings about HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have applied the TPB model to predict the safe sexual behaviors of young adults [17][18][19][20][21]. For example, a 2022 study from China used the TPB to identify the association between safe sexual behaviors and sexual knowledge in college students [18].…”
Section: Summary Statementmentioning
confidence: 99%
“…Many studies have applied the TPB model to predict the safe sexual behaviors of young adults [17][18][19][20][21]. For example, a 2022 study from China used the TPB to identify the association between safe sexual behaviors and sexual knowledge in college students [18]. The group with a higher score for sexual knowledge, attitudes, and safe sexual behavioral intentions showed safer sexual behaviors.…”
Section: Summary Statementmentioning
confidence: 99%